Mast cell tryptase enhances wound healing by promoting migration in human bronchial epithelial cells. Issue 1 (1st January 2021) - Mogren, Sofia; Berlin, Frida; Ramu, Sangeetha; Sverrild, Asger; Porsbjerg, Celeste; Uller, Lena; Andersson, Cecilia K
ABSTRACT: Epithelial damage and increase of intraepithelial mast cells (MC) are characteristics of asthma. The role of MC mediator tryptase and the protease-activated receptor-2 (PAR2) on epithelial wound healing is not fully investigated. Stimulation of bronchial epithelial cells (BECs) with tryptase promoted gap closure, migration and cellular speed compared to controls. Stimulated BECs had higher expression of migration marker CD151 compared to controls. Proliferation marker KI67 was upregulated in tryptase-stimulated BECs compared to controls. Treatment with PAR2 antagonist I-191 reduced gap closure, migration and cell speed compared to BECs stimulated with tryptase. We found that tryptase enhances epithelial wound healing by increased migration and proliferation, which is in part regulated via PAR2. Our data suggest that tryptase might be beneficial in tissue repair under baseline conditions. However, in a pathological context such as asthma with increased numbers of activated MCs, it might lead to epithelial remodeling and loss of function.